Pengaruh Siaran Langsung Dan Manfaat Yang Dirasakan Terhadap Niat Beli Melalui Kepercayaan Konsumen Pada Aplikasi Tiktok Shop - Juliana, Hellen (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine the direct effect of live streaming, the perceived benefits on consumer trust, to know the direct effect of live streaming, the perceived benefits, consumer trust on purchase intentions. As well as knowing the indirect effect of live streaming, the perceived benefits on purchase intention sthrough consumer trust in the Tiktok Shop application. Data collection was carried out by collecting information through a survey with a questionn aire. Question naires were distributed using the Google form via social media such as Whatsapp WA), Instagram (IG) and Telegram.The population in this study are users who have used and shopped in the Tiktok Shop application in the Jabodetabek area. Question naires were collected by 145 respondents, the data was then processed using the SmartPLS analysis tool. The results of this study indicate that live streaming has no effect on consumer confidence. While the perceived benefits have an influence on consumer confidence. Live streaming and consumer trust have an effect on purchase intentions. While the perceived benefits have no effect on purchase intention. live broadcast has no effect on purchase intention through consumer trust. Meanwhile, perceived benefits have an influence on purchase intentions through consumer trust. The contribution of this research results in consumer behavior, especially in the influencing factors, namely live streaming and consumer trust in the Tiktok Shop application.